Digital single market and digital performance of the EU - Saktaş, Sinem (My University, 2019)
The importance of the digital economy is increasing over the last decades. The digital economy is among the core elements of competitiveness of countries. The EU has also recognized the importance of the establishment of its own Digital Single Market. In line with the recent developments, the EU is transforming itself into a digital-based economy. The main objective of the study is to examine the transformation of the digital economy in the EU and the world. Thus, the study presents the development of the EU’s Digital Single Market and discusses its significance and contributions to the European economy. In this context, the study aims to assess the performance of the EU’s Digital Single Market by taking into account the main indicators of the digital economy. The study also takes into consideration the benefits of the EU’s Digital Single Market and barriers against its completion. E-commerce and taxation of ecommerce which are crucial dimensions of the EU’s Digital Single Market are also examined. In order to further develop its Digital Single Market, EU has to focus on the digital infrastructure investments and attempts related to the harmonization of the EU’s laws which abolish the barriers against well-performing Digital Single Market. It is expected that the Digital Single Market will offer many opportunities for the EU countries.

Son yıllarda dijital ekonominin önemi giderek artmaktadır. AB’de Dijital Tek Pazarı’nı oluşturması gerektiği gerçeğini kabul etmiştir. Dijital ekonomi ülkelerin rekabet edebilirliği için önemli belirleyiciler arasında yer almaktadır. Son gelişmelere paralel olarak AB, kendisini dijital tabanlı bir ekonomiye dönüştürmektedir. Çalışmanın temel amacı, AB’de ve dünyada hızla gerçekleşen dijital dönüşümün incelenmesidir. Çalışma AB Dijital Tek Pazarı’nın gelişim sürecini ele alarak Avrupa ekonomisi için önemi ve katkılarını tartışmaktadır. Bu bağlamda dijital ekonominin temel göstergeleri dikkate alınarak AB Dijital Tek Pazarı’nın performansı karşılaştırmalı olarak ölçülmeye çalışılmıştır. Çalışmada ayrıca AB Dijital Tek Pazarı’nın faydaları ve oluşturulması önündeki mevcut engeller ele alınmıştır. AB Dijital Tek Pazarı’nın iki önemli unsuru olan e-ticaret ve e-ticaretin vergilendirilmesi incelenmiştir. Çalışmada AB tarafından hedeflere ulaşıldığının ancak mevcut engellerin ortadan kaldırılmasına yönelik dijital altyapı yatırımlarına ve AB genelinde yasaların uyumlaştırılmasına daha fazla ağırlık verilmesi gerektiği sonucuna varılmıştır. AB Dijital Tek Pazar’ının ayrıca üye ülkeler için birçok fırsat sunması beklenmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Digitalization; Digital economy; European Union; Digital single market; Ecommerce; Dijitalleşme; Dijital ekonomi; Avrupa Birliği; Dijital tek pazar; E-ticaret